Manipulation of the Upper Respiratory Microbiota to Reduce Incidence and Severity of Upper Respiratory Viral Infections: A Literature Review - Nesbitt, Henry; Burke, Catherine; Haghi, Mehra (Frontiers in Microbiology, 2021)
There is a high incidence of upper respiratory viral infections in the human population, with infection severity being unique to each individual. Upper respiratory viruses have been associated previously with secondary bacterial infection however, several cross-sectional studies analysed in the literature indicate that an inverse relationship can also occur. Pathobiont abundance and/or bacterial dysbiosis can impair epithelial integrity and predispose an individual to viral infection. In this review we describe common commensal microorganisms that have the capacity to reduce the abundance of pathobionts and maintain bacterial symbiosis in the upper respiratory tract and discuss the potential and limitations of localised probiotic formulations of commensal bacteria to reduce the incidence and severity of viral infections.